(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The majority of the world’s natural water sources are not always safe to consume untreated. Raw water from rivers, lakes, ponds, and groundwater can include microorganisms. Waterborne diseases can be contracted by consuming it when pathogens in the water are spread through a drinking water distribution system. As it guarantees that water is free of dangerous microorganisms that cause water-borne diseases, disinfection is an essential water treatment technique. Different disinfection techniques are used to inactivate germs to fight waterborne illnesses. The primary goal of this essay is to describe various disinfection techniques, their applicability, limitations, and factors affecting the disinfection process. Chlorine by products and the effects of chlorine by products on people.